Influences of Firm Orientations on Sustainable Supply Chain Management - Mariadoss B. (2017)
© 2016 Elsevier Inc. Building on stakeholder theory, we propose and test an integrative model that incorporates the relationships between a firm's orientations and sustainable supply chain practices [i.e., sustainable purchasing practices (SPPs) and sustainable supply practices (SSPs)], and interactions between the different firm orientations as related to such sustainable practices. We empirically test our hypotheses in a two-phase survey of 149 managers in the U.S. manufacturing and service industries. Our findings reveal that a firm's environmental and cultural orientations affect its SPPs and SSPs, while local community orientation drives SPPs only in large firms. The results also suggest synergistic effects of environmental and cultural orientations on SPPs and SSPs, while societal orientation positively moderates the effect of cultural orientation on SSPs. Moreover, our findings demonstrate the moderating effect of firm business type on the relationships between cultural orientation and SPPs and SSPs.